Hybrid rocket performance with varying additive concentrations - Kafafy, Raed; Azami, Muhammad Hanafi; Idres, Moumen (2013)
A hybrid rocket motor represents a compromise between a solid rocket motor and a liquid rocket motor in terms of its performance. In addition, hybrid rockets are featured by throttling capability, increased safety, moderate cost and benign environmental impact. However, low regression rate is a major drawback of hybrid rocket performance. Adding additives to the hybrid rocket fuel is one possible solution to this matter. To investigate the characteristics of hybrid rocket performance we develop a generic simulation algorithm based on a legacy interior ballistic model. MATLAB® environment was used to develop the design and performance analysis codes, and visualize the temporal variation of performance characteristics. The simulation algorithm is used to predict the performance of hybrid rocket using different types of fuels with varying metallic additive concentrations. To increase heat conduction at localized head, higher additives intensity is doped, giving adequate burning throughout the fuel. This paper also presents experimental results obtained from a laboratory scale hybrid rocket motor which employs paraffin wax fuel doped with metallic additives with varying concentrations along the hybrid rocket motor axis and gaseous oxygen as an oxidizer. Experiments are carried out to investigate how varying the additive concentration affects the regression rate and overall performance. Initial investigation reveals that varying the distribution of metallic additive concentration can improve the regression rate.